SISTEM PENGELOLAAN DAN PELAYANAN TERHADAP KEPUASAN PEDAGANG DI PASAR SENTRAL RAPPANG KABUPATEN SIDENRENG RAPPANG - Adam Latif; Samsul Samsul (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
The main study in this research is the management system and service to the satisfaction of traders in Rappang Central Market of Sidenreng Regency. The research was conducted with the aim to know the management system and service to the satisfaction of merchant in Pasar Sentral Rappang. The type of research used is descriptive quantitative with data collection method that is survey research method through instrument instrument such as, observation, questionnaire and documentation, with respondents ie traders remain in the central market. Data analysis technique used data analysis using five likert scale which have been modified by the writer. The result of research shows the variable of management of central market management system of Rappang of Sidenreng Rappang Regency with the result of